2022
DOI: 10.1101/2022.01.26.22269849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence of Hepatitis B and C Viruses Among the Scavengers in Kwara State, Nigeria

Abstract: Background. Poor economic situations in developing nations had made scavenging a means of livelihood for millions of youth and women across the globe. Lack of proper source segregation of wastes in developing countries has increased the potential for the transmission of pathogens like Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV). Objectives. This study addressed issues relating to waste scavenging, the potential risk in waste scavenging work and seroprevalence of Hepatitis B and C Virus and its relation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…Another study also reported a higher rate (38.8) of HCV infection in people with primary education than in other categories. Our results for other education categories do not agree with this study [ 16 ]. Other studies also reported a high rate of HCV in solid waste collectors having secondary education from India [ 15 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Another study also reported a higher rate (38.8) of HCV infection in people with primary education than in other categories. Our results for other education categories do not agree with this study [ 16 ]. Other studies also reported a high rate of HCV in solid waste collectors having secondary education from India [ 15 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In our present study, we found a high rate of HCV infection in young people (≤40 years) than in aged persons, which is in agreement with Wanjari and other studies [ 10 , 15 ] stating that the majority of respondents are between 18 and 39 years. Also, another study from India published data from most young people [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy-metal contamination of agricultural soils has become a significant environmental concern in human cultures, particularly in developing nations, at the same time as the growth and expansion of industry, mining operations, and excessive use of chemical fertilizers [25][26][27][28][29][30][31][32][33][34][35]. Studies have demonstrated that anthropogenic activities such as improper waste management [36][37], industrial, mining, agricultural, and domestic activities as well as geogenic processes like weathering of rock minerals, rainfall intensity, leaching, and local geology of the aquifer [1][2][3][4][5][6][7][8][9][10][11][12][13] are the major controls on groundwater quality. Groundwater was severely contaminated as a result of excessive and unsustainable groundwater extraction for drinking and irrigation, irrigation runoff, surface contaminants permeating the groundwater system, a high rate of evaporation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…While, municipal wastes are mixed and unsegregated at points of generation, undermining effective management when it comes to treatment and disposal practices. Indiscriminate disposal and sorting of mixed wastes by scavengers have the potential for increased environmental exposure to air, water and soil pollution [9]. The improper waste management also contributes to the contamination of soil while its substantial metal contents are washed away by runoff into water bodies not limited to the streams and rivers thereby making human, animals, plants and the marine environment prone to environmental health risks.…”
Section: Introductionmentioning
confidence: 99%